Innovation in Science Learning Based on Eco Disaster Literacy through a Design Based Research Approach to Improve Environmental Care Attitudes and Problem Solving Skills of Elementary School Students - Arna Juwairiyah; Insih Wilujeng; Woro Sri Hastuti; Chairan Zibar L.Parisu (CV. Gerasi Insan Nusantara, 2026)
This study aimed to develop and evaluate an eco-disaster literacy–based science learning model using a Design-Based Research (DBR) approach to improve environmental awareness and problem-solving skills of elementary school students. The research was conducted at SD Negeri 1 Laousu, Konawe Regency, Southeast Sulawesi, involving 40 fifth-grade students. The DBR process included four stages: analysis, design, implementation, and evaluation. Data were collected through questionnaires, problem-solving tests, observations, and interviews. The findings showed that the learning model was highly valid, with Aiken’s V values ranging from 0.85 to 0.89, and highly practical, indicated by 92% implementation and 90% positive student responses. The model was also effective in improving student learning outcomes. Environmental awareness increased in the moderate category (N-Gain = 0.57), while problem-solving ability improved in the high category (N-Gain = 0.70). The t-test results showed significant differences between pretest and posttest scores (p < 0.05), indicating the effectiveness of the developed learning model.